Brill's Companion to Valerius Flaccus : Brill's Companion to Valerius Flaccus - Heerink, Mark (Brill's Companions in Classical Studies, 2014)
Contents -- Acknowledgements -- Notes on Contributors -- Chapter 1 Introduction -- Part 1 Text, Language and Poetic Techniques -- Chapter 2 Utere bono tuo feliciter: The Textual Transmission аnd Manuscript History оf Valerius Flaccus' Argonautica -- Chapter 3 Poet and Readers: Reflections on the Verbal and Narrative Art of Valerius Flaccus' Argonautica -- Chapter 4 Authorial Poetics in Valerius Flaccus' Argonautica -- Chapter 5 Valerius Flaccus, Virgil and the Poetics of Ekphrasis -- Part 2 Themes and Contexts -- Chapter 6 Myth and Mythopoesis in Valerius Flaccus' Argonautica -- Chapter 7 War and Love in Valerius Flaccus' Argonautica -- Chapter 8 Philosophical Ideas in Valerius Flaccus' Argonautica -- Chapter 9 Romanas veluti saevissima cum legiones Tisiphone regesque movet: Valerius Flaccus' Argonautica and the Flavian Era -- Part 3 Characters -- Chapter 10 A Hero with a Sandal and a Buskin: The Figure of Jason in Valerius Flaccus' Argonautica -- Chapter 11 Medea: From Epic to Tragedy -- Chapter 12 Teamwork, Leadership and Group Dynamics in Valerius Flaccus' Argonautica -- Chapter 13 My Family and Other Enemies: Argonautic Antagonists and Valerian Villains -- Part 4 Latin Intertexts -- Chapter 14 Virgilian Prophecy and the Reign of Jupiter in Valerius Flaccus' Argonautica -- Chapter 15 Ovid and Valerius Flaccus -- Chapter 16 Lucan and Valerius Flaccus: Rerouting the Vessel of Epic Song -- Chapter 17 Valerius Flaccus and Seneca's Tragedies -- Chapter 18 The Epics of Statius and Valerius Flaccus' Argonautica -- Chapter 19 Valerius Flaccus in Silius Italicus -- Part 5 Reception -- Chapter 20 Interpres operis alieni? Giovan Battista Pio's Continuation of Valerius Flaccus' Argonautica -- Bibliography -- Abstracts of Chapters -- Index of Passages -- General Index.